T-X phase diagram of (NH4)2SO4/H2O - Yurtseven, H.; Enginer, Y.; Sen, S.; Salihoglu, S. (Scientific Publ-India, 2007)
Using the mean field theory, we obtain the phase line equations for the liquid-solid I, liquid-solid II and solid I-solid II transitions in (NH4)(2)SO4/H2O. We fit our phase line equations to the experimental T-X phase diagram of this system. Thus, we are able to obtain the temperature and concentration dependencies of the order parameters and the free energies in this system.
Keywords: phase diagram; ammonium sulfate; mean field theory